The Use of Cheques in the European Union: A Cross-Country Analysis - Silva, Vânia (2018)
The use of cheques has been declining in the European Union (EU), along increased integration in the payments field. This trend is not uniform across the EU, and some countries have implemented policies to discourage the use of cheques due to its considerable social costs and risks. This paper provides a cross-country analysis for the period 2000–2012 of the determinants of cheque usage, measured both as per capita number and share of payments. Special attention is given to the effects of the application of fees in a framework where unfunded cheques are considered as an autonomous type of crime in some EU countries. Our results suggest that the existence of fees influences negatively cheque usage, even when there are legal elements that increase its security.